2022
DOI: 10.1186/s13287-022-03030-8
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal stem cells improve liver fibrosis and protect hepatocytes by promoting microRNA-148a-5p-mediated inhibition of Notch signaling pathway

Abstract: Background Mesenchymal stem cells (MSCs) are considered to be a potential therapeutic tool for liver fibrosis. Inhibiting the activation of hepatic stellate cells (HSCs) and protecting hepatocytes are important mechanisms for the anti-fibrotic effect of MSCs. However, how MSCs inhibit liver fibrosis by regulating the expression of microRNAs (miRNAs) has not been fully clarified. Methods Transforming growth factor-β1 (TGF-β1)-activated HSCs LX-2 wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 48 publications
0
13
0
Order By: Relevance
“…Recently, Song et al conducted animal studies and found that TB001, a dual glucagon like peptide-1 receptor/glucagon hormone receptor (GLP-1R/GCGR) agonist, alleviated liver fibrosis by blocking HC apoptosis [ 30 ]. Zhou et al found that treatment with human umbilical cord mesenchymal stem cells (HUC-MSCs) could protect HCs, inhibit HC apoptosis, and alleviate BDL-induced liver fibrosis in mice by upregulating the expression of miR-148-5p [ 31 ]. Zhang et al determined the lncRNA expression profiles in livers of fibrotic and normal mice by lncRNA microarray and qPCR.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Song et al conducted animal studies and found that TB001, a dual glucagon like peptide-1 receptor/glucagon hormone receptor (GLP-1R/GCGR) agonist, alleviated liver fibrosis by blocking HC apoptosis [ 30 ]. Zhou et al found that treatment with human umbilical cord mesenchymal stem cells (HUC-MSCs) could protect HCs, inhibit HC apoptosis, and alleviate BDL-induced liver fibrosis in mice by upregulating the expression of miR-148-5p [ 31 ]. Zhang et al determined the lncRNA expression profiles in livers of fibrotic and normal mice by lncRNA microarray and qPCR.…”
Section: Discussionmentioning
confidence: 99%
“…The levels of alanine aminotransferase (ALT), aspartate aminotransferase (AST), and alkaline phosphatase (ALP) in the serum were assayed using commercial kits (Shanghai Enzyme Link Biotechnology Co., Ltd., Shanghai, China). 20 …”
Section: Methodsmentioning
confidence: 99%
“…This indicates that the exosomal miR-150 has antifibrotic activity through targeting of the TGF-β pathway. Zhou et al [ 91 ] co-cultured HSCs with human umbilical cord MSCs and found that expression of miR-148a-5p in HSCs was significantly upregulated, which decreased liver fibrosis by inhibiting Notch2 in vivo and in vitro .…”
Section: Potential Application Of Ncrnas For the Treatment Of Liver F...mentioning
confidence: 99%